Fossilized melanosomes in the Crato Formation (Araripe Basin, Cretaceous), Brazil: Taphonomy and palaeobiological implications - Prado, Gustavo Marcondes Evangelista Martins (2023)
The preservation of organic compounds is noteworthy in the geologic record as these components usually are lost soon after decay is established. Among these, melanin is a delicate and highly heterogeneous natural pigment, which can be found in virtually all organisms. This pigment, or biochrome, is generally found inside the organelles called melanosomes, which size ranges from 0.1 to 2.0 µm, and whose shape varies in accordance with the melanin produced. Overall, these subcellular particles can be divided into two forms: the spherical phaeomelanosomes that produce the red-yellowish-coloured phaeomelanin; and the rod-shaped eumelanosomes that produce the black-brownish eumelanin. Despite its delicate nature, melanosomes were found in fossils of animals from many deposits around the world, and these organelles allowed inferences about the taphonomy of these (and others) organic molecules, as well as the biological role of colour patterns in addition to their relationship with the palaeoenvironment. In Brazil, the Cretaceous Crato Formation (Araripe Basin, NE) is accounted for most cases of these organelles. However, only a few taxa have been examined, and in a few studies, whilst important palaeobiological, palaeoecological, and taphonomic aspects still remain obscure. In response to this issue, in this thesis, a comprehensive number of fossils (a total of 87 specimens consisting of two fish, one frog, two pterosaurs, and 82 isolated feathers) were analysed focusing on the identification of melanosomes and melanin using multiple analytical and statistical approaches. Overall, it was revealed that most soft tissues exhibited the presence of fossilized oblate to elongated microbodies. These occur as solid or external moulds and are preserved as kerogen/eumelanin, calcium phosphate, and iron oxyhydroxide, (i.e., limonite). Eumelanin was only detected in carbonized and phosphatized specimens, whereas the limonite-rich fossils only showed their mineral signature with no signal of melanin or other pigments (e.g., carotenoids ). Therefore, due to dimensions and chemistry, in addition to the remarkable similarities with melanosomes from tissues of modern animals, the microbodies observed in these fossils were then identified as the fossilized analogues of these organelles. Chemical analysis indicated that the microbody\'s physical integrity and eumelanin retention inside varied according to its composition/mineralogy. While the kerogeneous and phosphatized microbodies remained physically pristine, those limonite-rich ones exhibited signatures of mineralization, which its extent could lead to their disintegration into scattered single acicular crystals. In kerogenized and phosphatized granules, it was recognized that diagenetic processes (e.g., increase in temperature) were responsible for the degradation of eumelanin into a larger and disordered polymer; whereas, in limonite-rich fossils, this biochrome was totally degraded. In sum, eumelanin and eumelanosomes in these fossils, possibly played a fundamental role in photoprotection, such as in the case of fish eyes and frog skin, and display or camouflage in feathers and pterosaurs. In conclusion, this investigation provided a holistic view of the taphonomy and the possible role of melanin and melanosomes in extinct taxa of the Crato Formation. This thesis also showed that the Palaeocolour studies have great potential to broaden and expand knowledge, which also suggests its applicability to other fields of science, such as astrobiology and geobiology.